Les voyageurs occidentaux à la découverte de l’altérité musulmane au bas Moyen Âge - Nissaf Sghaïer (Frontière·s)
In 1432, Bertrandon de la Broquière, the first Sharp Squire of the Duke of Burgundy Philippe le Bon, was sent in the Middle East on a reconnaissance mission. At the Duke’s request, Bertrandon wrote a travel story from his journey – which led him to travel overland through the Near East, Asia Minor, the Balkans and Central Europe – entitled Le Voyage d’Outremer.This narrative distinguishes itself by the richness of its descriptions, based on Bertrandon’s observations and discussions during his trip.It is therefore a significant testimony on knowledge and perception of the Muslim otherness in the first half of the 15th century written by a noble Burgundian.This article analyses how Bertrandon de la Broquière managed to get closer to various Muslim societies he met, in order to convey a description that goes beyond stereotypes.